The Star trek book - Ruditis, Paul; Galden-Stone, Sandford (Dk Publishing, 2016)
Celebrate 50 years of one of the longest running and beloved sci-fi franchises with "The Star Trek Book." This comprehensive guide to the series delves into the myriad worlds and different dimensions visited by the crew of the U.S.S. Enterprise. Perfect for fans of the various "Star Trek" TV series, including "The Next Generation," "Deep Space Nine," "Voyager," and "Enterprise," "The Star Trek Book" details everything you need to know about 50 years of excitement and adventure on the final frontier.